Agricultural production structure, market conditions and farmers’ nutritional intake in rural China - Yue WAN; Hao HU; HU Wuyang (Journal of Integrative Agriculture, 2022)
Nutrition poverty alleviation is an effective measure to improve the nutritional status of economically disadvantaged individuals, fundamentally improving their health and reducing poverty. Based on the Entitlement Theory and using the China Health and Nutrition Survey (CHNS) data, this paper examines the relationship between farmers’ nutritional intake, production structure and regional market conditions. Results show that farmers with diversified production have better nutritional intake than those who specialize. Furthermore, the correlation between regional market conditions and nutritional intake varies between economically disadvantaged and non-economically disadvantaged households. Market conditions significantly influence the carbohydrate and fat intake of economically disadvantaged households and are positively associated with the dietary structure and nutritional intake of non-economically disadvantaged ones. Moreover, income is positively correlated with the nutritional intake of non-economically disadvantaged households but not with economically disadvantaged ones.